Twin reverse arterial perfusion sequence, a diagnostic dilemma in a low-resource setting: a case report - Enabudoso, Ehigha J.; Idiagbonya, Nosakhare S.; Oriakhi, Victor I.; Iweka, Reuben O. (International Journal of Research in Medical Sciences, 2025)
Twin reverse arterial perfusion (TRAP) sequence is a unique but rare complication of monochorionic twin gestation characterized by absence of complete cardiac structure (“acardia”) of one twin while the second and normal twin (“pump twin”) appears normal and supplies both circulations. Diagnosis requires skill and a high index of suspicion. We report a 37-year-old gravida 3 para 2 lady who presented with an initial obstetric scan finding of twin gestation with severe polyhydramnios and single twin demise at 18-weeks gestation. Subsequent feto-maternal specialist ultrasound review at 23 weeks gestation revealed structurally normal live twin but structurally abnormal dead twin with indistinct features with possible twin-twin transfusion syndrome. Despite attempts at medical amnioreduction, she developed respiratory distress and preterm contractions following worsening polyhydramnios. She subsequently had preterm delivery at 26 weeks gestation of a live twin that suffered early neonatal death and an acardiac dead twin. This report highlights an unnecessarily missed diagnosis of a rare complication of twin gestation. It buttresses the need for training and ultrasound competence. This TRAP sequence was missed antenatally despite serial scans. Where feasible, multiple gestation requires ultrasound evaluation by subspecialty teams in feto-maternal medicine for early diagnosis to plan for adequate management. This report further highlights the need for sonographers and obstetric sonologists to deliberately evaluate for abnormalities including TRAP sequence especially in monochorionic twin pregnancies. Such evaluation will lead to early diagnosis and institution of needed management.